Prevalence of underweight and overweight among school-aged children and it's association with children's sociodemographic and lifestyle in Indonesia - Syahrul Syahrul (International Journal of Nursing Sciences, 2016)
Objectives: Underweight remains a health problem among Indonesian children, and the incidence of overweight continuously increases. This study aims to determine factors associated with underweight and overweight in school-aged children in Indonesia. Methods: This study is a cross-sectional investigation on parents and children aged 6–13 years in elementary schools in Makassar, Indonesia. The participants included 877 children and their parents. Anthropometric data were obtained using standardized equipment, and sociodemographic and lifestyle data were determined using a questionnaire. The nutritional status of the children was assessed based on the child growth standard prescribed by the WHO. Results: The prevalence rates of underweight and overweight among the children were 14.5% and 20.4%, respectively. Underweight was more prevalent in boys. Factors such as mother's level of education, having an underweight father, and playing outdoors on weekends for more than 2 h were significantly associated with underweight children. By contrast, mothers with high levels of education, overweight parents, sleeping for less than 9 h, and playing outdoors on weekends for less than 1 h were significantly associated with overweight children. Conclusions: The prevalence of underweight and overweight among school-aged children in Makassar, Indonesia is high. These conditions are associated with the sociodemographic characteristics of children and parents, as well as the lifestyle of children. Parental characteristics and children's lifestyle should be considered when planning prevention and intervention programs for underweight or overweight children.